Classroom Seat Proximity Predicts Friendship Formation - Faur, Sharon; Laursen, Brett (Frontiers in Psychology, 2022)
The present study tests the hypothesis that friendships form on the basis of classroom seating propinquity. Participants included 235 students (129 boys, 106 girls) in grades 3-5 (ages 8-11) who nominated friends at two time points (13-14 weeks apart). Teachers described seating arrangements. Concurrent analyses indicated that students sitting next to or nearby one another were more likely to receive friend nominations and be involved in reciprocated friendships than students seated elsewhere in the classroom. Longitudinal analyses indicated that classroom seating propinquity was associated with the formation of new friendships. Most results for randomly selected outgoing friend nominations and randomly selected reciprocated friend dyads were replicated in analyses that included all friend nominations and all friend dyads.